Perceived economic prospects during the early stage of COVID-19 breakout - Li, Keyang (2023)
How does a new epidemic affect individuals' expectations on economic prospects in the early stage of the breakout? We implemented an incentivized longitudinal online survey soon after the outbreak of the coronavirus disease 2019 (COVID-19) epidemic in China to answer this question. Results show that fewer new confirmed COVID-19 cases significantly increase individuals' expectations on gross domestic product and consumer price index growth rates. Our finding provides evidence that at the early stage of an unfamiliar epidemic, containing the spread of the disease may help to maintain positive economic expectations among individuals.